Unraveling determinants of integrated farming systems adoption for sustainable livelihood and dietary diversity - Raghavendra, K. J.; John, Jacob; Jacob, D.; Rajendran, T.; Prusty, A. K.; Ansari, Meraj Alam; Ravisankar, Natesan; Kumar, Sunil; Singh, Raghuveer; Shamim, Mohammad; Punia, Peyush; Nirmal,; et al. (Frontiers in Nutrition, 2024)
Introduction Over the years, smallholder farmers have faced more vulnerability to risk and uncertainty in India due to their dependence on cereal crops. One way to reduce this risk is through diversified agriculture, integrating different practices for efficient resource utilization, and adopting a farming systems approach. An integrated farming system (IFS) is one such technique that provides year-round income from different components of enterprises. However, the decision to adopt IFS may be determined by several characteristics of farmers, which needs to be delineated through impact analysis to harness the benefits of a systems approach. Methods This study analyzes the economic effects of integrated farming systems and assesses their determinants, as well as the dietary diversity patterns of farmers in two states of southern India, i.e., Kerala and Tamil Nadu. A multistage sampling technique was used to obtain cross-sectional data from 367 farmers randomly chosen from one district in Kerala and two districts in Tamil Nadu. The participants have Crop + Horticulture + Animal husbandry (45.45%) as their major system, whereas non-participants have Crop + Animal husbandry (44.35%) as their predominant system. Coarsened exact matching and logit regression methods were used to evaluate the economic impacts of IFS and its influencing factors. Results The findings of the study indicate that age, education, livestock holding, access to credit, and plantation area have a positive and significant effect on participation by farmers in the program. The matching results show that adoption of IFS resulted in a significant economic impact, generating an additional gross income of Rs. 36,165 ha−1 and a net income of Rs. 35,852 ha−1 and improving the dietary diversity of farm households by 8.6% as compared to non-adopters. Discussion This study suggests that IFS is a promising approach for improving farmers' livelihoods, economic gains, and nutritional security. Therefore, the integrated farming systems models need to be upscaled through the convergence of government schemes in other regions of India to support smallholder farmers' farming.